Remote Monitoring in Clinical Trials During the COVID‐19 Pandemic. Issue 5 (8th July 2020) - Izmailova, Elena S.; Ellis, Robert; Benko, Christopher
Abstract : The coronavirus disease 2019 (COVID‐19) pandemic has rapidly challenged the pharmaceutical industry to implement remote clinical trials. The industry's lack of extensive experience with remote measurements initiates multiple questions about how to select candidates for remote collection, their validity, and regulatory implications of moving certain assessments to a remote mode. We propose a decision tree for migration of clinic to remote assessments and highlight activities required to ensure that these measurements are valid, safe, and usable.